The lesser Jihads bringing the Islamist extremist fight to the world - Gurski, Phil (Rowman & Littlefield, 2017)
The Lesser Jihads examines conflict through the lens of Islamist terrorist groups. Bringing together in one volume different conflicts where terrorist groups are active worldwide, this text introduces the world and thinking of Jihadists while highlighting a number of seldom reported cases